Inverse Association between Iron Deficiency and Glycated Hemoglobin Levels in Ghanaian Adults—the RODAM Study. Issue 7 (20th May 2020) - Lyons, Julia; van der Linden, Eva L; Meeks, Karlijn; Beune, Erik; Smeeth, Liam; Bahendeka, Silver; Spranger, Joachim; Klipstein-Grobusch, Kerstin; Mockenhaupt, Frank P; Danquah, Ina; Agyemang, Charles
ABSTRACT: Background: Glycated hemoglobin (HbA1c) is often used to diagnose type 2 diabetes (T2D), but studies show that iron deficiency (ID) is associated with elevated HbA1c in the absence of hyperglycemia. It is unknown whether ID prevalence varies between sub-Saharan African populations living in different locations and whether ID influences HbA1c levels in these populations. Objectives: We assessed the prevalence of ID among Ghanaian migrants in Europe and nonmigrant Ghanaians, and the influence of ID on HbA1c categories among Ghanaians without T2D. Methods: We used the database from the cross-sectional RODAM (Research on Obesity and Diabetes among African Migrants) study. This contained data on 3377 Ghanaian men and women aged 25–70 y living in urban and rural Ghana and Ghanaian migrants living in Amsterdam, London, and Berlin. ID was defined as ferritin < 15 ng/mL or, if C-reactive protein was ≥5 mg/mL, as ferritin < 30 ng/mL according to the WHO. We used binary logistic regression to assess differences in ID between sites and its association with clinically defined HbA1c categories (<5.5%, ≥5.5% to <6.5%, ≥6.5%). Men and women were analyzed separately. Results: The prevalence of ID was higher in migrant [28.4%; adjusted OR (aOR): 3.08; 95% CI: 2.04, 4.65)] and urban (23.2%; aOR: 2.37; 95% CI: 1.56, 3.59) women than in rural women (11.9%). Among women, ID was associated with higher odds of HbA1c ≥ 5.5% to <6.5% in the absence of hyperglycemia (aOR: 1.43; 95% CI: 1.08, 1.87). This association was not found in men. Conclusions: Further research is needed to identify factors underlying the high prevalence of ID among urban and migrant Ghanaian women, and the association of ID with HbA1c ≥ 5.5% to <6.5% in women. In addition, our study reinforces the need to consider iron concentrations if interpreting HbA1c among African populations.